Teoria dos jogos evolucionários e o surgimento da cooperação: dinâmicas inovativas e jogos mistos - Marco Antonio Amaral (2017)
How cooperation emerges among individuals is still an open question, and it reaches disciplines as different as evolutionary biology and economy. The mathematical framework of game theory is a good way to approach the dilemma of being altruistic and sacrifice for the group or being selfish and betray the other for a benefit. In this work we study how cooperation behaves in the presence of payoff fluctuations in imitative dynamics. We found that cooperation flourishes in the presence of such fluctuations, showing a strong stability in face of inevitable environment fluctuations. We also propose two new strategy updade models inpired by the Ising model; the winstay- lose-shift model with dynamical ambition and the innovative Logit model. We characterized the population dynamics of such models extensively, using Monte Carlo dynamics and the master equation approach. We found that inovative models have similar results to recent experiments with humans, mainly regarding their independence of the interaction topology.